HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU SEKSUAL REMAJA PUTRI DI SMA NEGERI 2 KOTA LHOKSEUMAWE - Kartini Putri, Hendrika Wijaya; Elizar, Elizar (Indonesian Trust Health Journal, 2023)
Adolescent reproductive health is one of the factors that can influence premarital adolescent sexual behavior. This phenomenon indicates that adolescent sexual behavior in various provinces is increasing due to the lack of knowledge of adolescents regarding reproductive health. The purpose of this study was to determine the relationship between knowledge and attitude with the sexual behavior of young women at SMA Negeri 2 Lhokseumawe City. This type of research is an analytic observational study using a cross sectional approach. The population in this study were 96 students of SMA Negeri 2 Lhokseumawe City in 2021 class XI. Data analysis in this study used unvariate and bivariate analysis The findings of this study were obtained for the knowledge of adolescents p value <0.05 which means there is a relationship between the knowledge of young women and sexual behavior of young women, for attitudes obtained p <0.05 which means there is a relationship between the attitudes of young women and the behavior of young women. It is hoped that students will take part in training and extracurricular activities at school such as participating in the Adolescent Reproductive Health program to increase adolescent knowledge about risky sexual behavior. Abstrak Kesehatan reproduksi remaja merupakan salah satu faktor yang dapat mempengaruhi perilaku seksual remaja pranikah. Fenomena ini menunjukkan bahwa perilaku seksual remaja diberbagai provinsi semakin meningkat dikarenakan kurangnya pengetahuan remaja mengenai kesehatan reproduksi. Tujuan penelitian ini adalah untuk mengetahui hubungan pentahuan dan sikap dengan perilaku seksual remaja putri di SMA Negeri 2 Kota Lhokseumawe. Jenis penelitian ini adalah penelitian observasional analitik dengan menggunakan metode pendekatan cross sectional. Populasi dalam penelitian ini adalah siswi SMA Negeri 2 Kota Lhokseumawe kelas XI yang berjumlah 96 orang. Analisis data dalam penelitian ini menggunakan analisis unvariat dan bivariat Temuan penelitian ini diperoleh Pengetahuan remaja p value < 0,05 yang berarti ada hubungan antara pengetahuan remaja putri dengan perilaku seksual remaja putri, untuk sikap diperoleh p < 0,05 yang berarti ada hubungan antara sikap remaja putri dengan perilaku remaja putri. Diharapkan siswa mengikuti pelatihan dan kegiatan ekstrakurikuler di sekolah seperti mengikuti program Kesehatan Reproduksi Remaja untuk meningkatkan pengetahuan remaja tentang perilaku seksual berisiko.